1999
DOI: 10.1098/rspb.1999.0685
|View full text |Cite
|
Sign up to set email alerts
|

Hybridizing Old and New World camelids: Camelus dromedarius x Lama guanicoe

Abstract: Thirty female dromedary camels were inseminated on a total of 50 occasions with 2^4 ml of fresh guanaco semen diluted with an equal volume of commercially available camel semen extender. Similarly, nine female guanacos were inseminated on 34 occasions with 4^6 ml of fresh, diluted camel semen. Only two of the dromedary females conceived; one aborted a female foetus on day 260 of gestation and the other gave birth to a stillborn female calf on day 365. Six conceptions occurred in the female guanacos. Two of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 20 publications
0
33
0
1
Order By: Relevance
“…They found the GTG-banding patterns of the bactrian, llama and guanaco quite identical to each other, thus suggesting that the amount of divergent evolution which has occurred in the family Camelidae has been accomplished, mainly, by single gene mutations or minor chromosomal rearrangements. However, a recent report on failure of hybridization between a female dromedary and a gua- naco stallion (Skidmore et al, 1999) would indicate that, despite the extensive similarity in the diploid number and chromosome banding, sufficient genetic change has taken place to make the pairing of homologous chromosomes no longer possible. This finding points out the need to explore chromosome homologies within the family Camelidae by using more effective techniques, such as high resolution banding, cross-species fluorescent in situ hybridization (ZOO-FISH) with chromosome specific painting probes and/or chromosome markers, and gene mapping.…”
Section: Resultsmentioning
confidence: 99%
“…They found the GTG-banding patterns of the bactrian, llama and guanaco quite identical to each other, thus suggesting that the amount of divergent evolution which has occurred in the family Camelidae has been accomplished, mainly, by single gene mutations or minor chromosomal rearrangements. However, a recent report on failure of hybridization between a female dromedary and a gua- naco stallion (Skidmore et al, 1999) would indicate that, despite the extensive similarity in the diploid number and chromosome banding, sufficient genetic change has taken place to make the pairing of homologous chromosomes no longer possible. This finding points out the need to explore chromosome homologies within the family Camelidae by using more effective techniques, such as high resolution banding, cross-species fluorescent in situ hybridization (ZOO-FISH) with chromosome specific painting probes and/or chromosome markers, and gene mapping.…”
Section: Resultsmentioning
confidence: 99%
“…Gray (1972) reported that interbreeding can take place between the two Old World camelids with fertile offspring, and the same is true for the New World camelids. More recently, it was shown that representatives of the Old World camelids and New World camelids can cross-hybridize via artificial insemination (Skidmore et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila (11,38) and mammals (39,40) many pairs of species that accumulated differences at Ϸ10 5 or more amino acid sites can produce viable or even fertile hybrids. This implies that between closely related species F Ͻ 10 Ϫ5 , in an apparent discrepancy with our estimate of F Ϸ 10 Ϫ1 .…”
Section: Preponderance Of Intramolecular Compensationmentioning
confidence: 99%